Gastarbeiter in Neuseeland - Die Pazifik-Insulaner - Kreisel, Werner (ERDKUNDE, 1983)
New Zealand has been a goal for immigrants throughout its history. The first settlers, and thus the indigenous population, were Polynesians (Maoris) who came to the previously uninhabited islands in a series of waves from Central Polynesia after 800 AD. European influence only began considerably later (with Cook's visit in 1769). As a British colony, New Zealand became in the 19th century a popular country for emigrants, mainly from Great Britain. The result is that Europeans today form the major part of the population and the native Maoris only represent a minority. The immigration of inhabitants of the Pacific island groups to New Zealand is a very recent development. There has been an expanding employment market in New Zealand since the sixties and this exercised a considerable attraction on the inhabitants of the Pacific Islands. There was thus a reservoir of manpower in the mostly economically underdeveloped groups of islands in the South Pacific which New Zealand's economy exploited to the full in times of prosperity. The result is that at present 2.9% of New Zealand's total population are Pacific Islanders. The Pacific Islanders in New Zealand have integration difficulties similar to those typical of immigrant workers in Central Europe. They are disadvantaged in several spheres as a visible minority; moreover, they have to struggle against considerable prejudices in public life. One of the Pacific Islanders' major problems is the adaptation of the traditional way of life in their homelands to New Zealand's modern economic system and western-orientated social structure. This raises obstacles to rapid assimilation and integration. The employment structure also displays a deficit in the higher professions and the incomes pattern a below-average proportion in the higher incomes bracket. The Pacific Islanders, who tend to form characteristic residential areas of their own particularly in the large towns of New Zealand, are therefore chiefly to be found among the lower social classes. Although the experience of Pacific Islanders in New Zealand is thus by no means exclusively positive, New Zealand's attraction is sufficient to reinforce further the immigration trend from the Pacific area. In view of the current economic recession, the New Zealanders feel obliged to discourage further immigration. The justification for this (familiar from Europe) is that in this way jobs are guaranteed for the domestic population, in this case the New Zealanders.